2013
DOI: 10.1128/aem.00509-13
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal and Survival of Flavobacterium psychrophilum PhagesIn Vivoin Rainbow Trout andIn Vitrounder Laboratory Conditions: Implications for Their Use in Phage Therapy

Abstract: Attention has been drawn to phage therapy as an alternative approach for controlling pathogenic bacteria such as Flavobacterium psychrophilum in salmonid aquaculture, which can give rise to high mortalities, especially in rainbow trout fry. Recently, phages have been isolated with a broad host range and a strong lytic potential against pathogenic F. psychrophilum under experimental conditions. However, little is known about the fate of phages at environmental conditions. Here, we quantified the dispersal and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 19 publications
3
41
0
Order By: Relevance
“…Bacteriophages could decrease the opportunities of bacterial infections and may be an ecological approach to solve the problem. Some research showed that bacteriophages possess the ability to control the pathogens and reduce fish mortality rates in low-temperature aquaculture (Castillo et al 2014;Madsen et al 2013;Castillo et al 2012). For example, Flavobacterium psychrophilum is a fish pathogen that causes cold water disease, and it was verified that the lytic bacteriophage infecting F. psychrophilum could control this pathogen in artificial laboratory conditions (Castillo et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Bacteriophages could decrease the opportunities of bacterial infections and may be an ecological approach to solve the problem. Some research showed that bacteriophages possess the ability to control the pathogens and reduce fish mortality rates in low-temperature aquaculture (Castillo et al 2014;Madsen et al 2013;Castillo et al 2012). For example, Flavobacterium psychrophilum is a fish pathogen that causes cold water disease, and it was verified that the lytic bacteriophage infecting F. psychrophilum could control this pathogen in artificial laboratory conditions (Castillo et al 2012).…”
Section: Discussionmentioning
confidence: 98%
“…Phages, which possess a different mode of action compared antibiotics, are expected to be an alternative to antibiotics (O'Flaherty et al, 2009). Controlling pathogens through the use of phages has been investigated for various applications such as therapeutic drugs for human, domestic animal, plants, hatchery fish, and food additives (Carvalho et al, 2010b;Gupta & Prasad, 2011;Addy et al, 2012;Chibeu et al, 2013;Madsen et al, 2013). However, studies on the growth inhibition of M. morganii by lytic phages have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have presented detailed characterization of bacteriophages with lytic capacity against F. psychrophilum, emphasizing the potential of phages to control the pathogen and reduce its impact on fish mortality (6)(7)(8). However, as seen for treatment with antibiotics, phage control of bacteria is also challenged by the development of bacterial resistance against bacteriophages.…”
mentioning
confidence: 99%